The effectiveness of mindfulness-based stress reduction (MBSR) on anxiety and depression in patients with multiple sclerosis (MS) - Ebrahimi, Alisaleh; Ghahari, Shahrbanoo (Chronic Diseases Journal, 2020)
BACKGROUND: Multiple sclerosis (MS) is a stressful event in life and anxiety and depression are common in these patients. Mindfulness-based stress reduction (MBSR) may help and reduce mood disorders in patients with MS. In this regard, the present study is carried out aiming to evaluate the effect of MBSR on anxiety and depression in women with MS. METHODS: This was a quasi-experimental study with a control group with the statistical population including all women with MS in Iran MS Society. 30 patients were selected and classified in two groups randomly. The test group participated in MBSR training program for 8 sessions and the control group did not receive this treatment. All patients in the two groups completed depression and anxiety scales before and after the intervention and the data were analyzed by the SPSS software. RESULTS: The results showed that the two groups were different in the scores of anxiety and depression scales after the intervention (P < 0.001). CONCLUSION: MBSR could reduce anxiety and depression in patients with MS.